Comparison of rescue techniques for failed chloral hydrate sedation for magnetic resonance imaging scans—additional chloral hydrate vs intranasal dexmedetomidine. Issue 3 (30th December 2015) - Zhang, Wenhua; Wang, Zixin; Song, Xingrong; Fan, Yanting; Tian, Hang; Li, Bilian
Summary: Background: Chloral hydrate, a commonly used sedative in children during noninvasive diagnostic procedures, is associated with side effects like prolonged sedation, paradoxical excitement, delirium, and unpleasant taste. Dexmedetomidine, a highly selective α ‐2 agonist, has better pharmacokinetic properties than chloral hydrate. We conducted this prospective, double‐blind, randomized controlled trial to evaluate efficacy of intranasal dexmedetomidine with that of a second oral dose of chloral hydrate for rescue sedation during magnetic resonance imaging (MRI) studies in infants. Methods: One hundred and fifty infants (age group: 1–6 months), who were not adequately sedated after initial oral dose of 50 mg·kg −1 chloral hydrate, were randomly divided into three groups with the following protocol for each group. Group C: second oral dose chloral hydrate 25 mg·kg −1 ; Group L and Group H: intranasal dexmedetomidine in a dosage of 1 and 2 mcg·kg −1, respectively. Status of sedation, induction time, time to wake up, vital signs, oxygen saturation, and recovery characteristics were recorded. Results: Successful rescue sedation in Groups C, L, and H were achieved in 40 (80%), 47 (94%), and 49 (98%) of infants, respectively, on an intention to treat analysis, and the proportion of infants successfully sedated in Group H was more than that of Group L ( P ˂ 0.01). There were no significant differences in sedation induction time; however, the time to wake up was significantly shorter in Group L as compared to that in Group C or H ( P < 0.01). No significant adverse hemodynamic or hypoxemic effects were observed in the study. Conclusion: Intranasal dexmedetomidine induced satisfactory rescue sedation in 1‐ to 6‐month‐old infants during MRI study, and appears to cause sedation in a dose‐dependent manner. Abstract :